Legal Proofs and Sharia Implementation of Aqiqah: A Normative and Empirical Analysis within Islamic Law and Social Reality - Faiz Fii Diin (Walidem Institute and Publishing (WIP), 2025)
Objective: The research aims to analyze the concept of aqiqah from the perspective of Islamic law through an examination of the postulates of shari'i and its implementation in contemporary Muslim society. Theoretical framework: This research is built on the basis of the approach of ushul fiqh and fiqh of worship, by placing the principles of maqasid al-shari'ah as a normative foundation. The concept of monotheism and obedience to the sunnah of the Prophet PBUH, is used as a frame in understanding the symbolic and social meaning of aqiqah as a form of gratitude for the birth of children and a form of social solidarity for Muslims. Literature review: Literature review is carried out by referring to classic works such as Al-Majmu' Syarh al-Muhadzdzab by Imam Nawawi, Fiqh al-Sunnah by Sayyid Sabiq, as well as contemporary references such as the fatwa of the Indonesian Ulema Council (MUI) and the National Sharia Council. The literature shows that aqiqah has a strong basis in authentic hadith, although there are differences of opinion regarding the time of implementation and the number of slaughtered animals. Method: using a qualitative approach through literature studies and field observations. Empirical data were obtained through interviews with religious leaders and aqiqah service actors in urban and rural areas to find out the understanding of the community and the variety of implementation practices. Results: It shows that the majority of people understand aqiqah as the sunnah of mu'akkadah with high spiritual and social value, but the practice in the field is often not fully in accordance with the provisions of fiqh, especially in terms of time, intention, and distribution of meat. Implications: This research is expected to be a reference for religious institutions, Islamic education, and aqiqah service actors in straightening out the understanding of authentic Islamic law and building religious awareness based on maqasid al-shari'ah. Novelty: This research lies in an integrative approach that combines normative analysis of classical texts of fiqh with empirical observations of the practices of modern society. Not only does it highlight the different views of scholars, but it also presents a contextual perspective that explains the dynamics of the transformation of aqiqah law from the classical period to the modern era.